Analisis Pengaruh Label Halal Terhadap Pemilihan Porduk Kosmetik (Make Up): Studi Kasus Mahasiswi Ekonomi Syariah Uin Sultan Maulana Hasanuddin Banten - Octaviana Dainy; Ismatul Hasanah; Siti Sopia; Hadi Peristiwo; Wahyu Hidayat (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The purpose of this research is to see how much influence the halal label has on the choice of cosmetic products (make up) among Islamic Economics students at UIN Sultan Maulana Hasanuddin Banten. This research uses quantitative methods and descriptive verification methods. This research information was collected through a survey distributed to 30 students of the Sharia Economics Study Program at UIN Sultan Maulana Hasanuddin Banten. The data in this research were analyzed using the IBM SPSS Statistics version 25 program. According to the research results, the halal label variable has a very large and beneficial influence on the choice of cosmetics. These results are viewed from the results of hypothesis testing on the accepted variables, which show that there is a strong positive influence of the halal label variable on the assessment of cosmetic selection.